2013
DOI: 10.1007/s00266-013-0197-y
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness, Compliance, Resilience, and Creep Deformation: Understanding Implant-Soft Tissue Dynamics in the Augmented Breast: Fundamentals Based on Materials Science

Abstract: The authors have found that the principles of the mechanics of materials can provide plastic surgeons with some clues for a predictable, long-lasting good result in breast augmentation and augmentation-mastopexy. Future studies are needed to develop these concepts and evaluate how they might individually determine the mid- and long-term outcomes of augmented breasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…The contact area increases on average 0.07 dm 2 (0.6%), and the force and pressure decrease substantially during the clamping phase, respectively 1.6 daN (9.3%) and 1.7 kPa (9.1%). This particular effect is known as creep motion, which is characteristic for viscoelastic soft tissues under compression [ 28 , 29 ]. From Figures 2 and 3 it can be observed that the decrease in force and pressure is steepest (quickest) directly after having reached the maximum force, and then gradually becomes less steep (slower).…”
Section: Resultsmentioning
confidence: 99%
“…The contact area increases on average 0.07 dm 2 (0.6%), and the force and pressure decrease substantially during the clamping phase, respectively 1.6 daN (9.3%) and 1.7 kPa (9.1%). This particular effect is known as creep motion, which is characteristic for viscoelastic soft tissues under compression [ 28 , 29 ]. From Figures 2 and 3 it can be observed that the decrease in force and pressure is steepest (quickest) directly after having reached the maximum force, and then gradually becomes less steep (slower).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the MSC signals were characterized by creep [54], which causes crosstalk between the active and nonactive (RS) motion recordings, thus attenuating the motion recognition accuracy. is situation is particularly severe in cases where the RS and HO movements of the subjects are being predicted (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…An appreciation of soft-tissue dynamics in the augmented breast also assists in predicting the final outcome and potential complications. 35 The implant type, shape, and profile determine the distribution of fill within the breast. The distances from the sternal notch to the nipple and from the nipple to the inframammary fold (IMF) under stretch can quantify asymmetry and the ptosis grade.…”
Section: Preoperative Preparationmentioning
confidence: 99%